Exploring Orodispersible Films Containing the Proteolysis Targeting Chimera ARV-110 in Hot Melt Extrusion and Solvent Casting Using Polyvinyl Alcohol - Valentina Meloni; Laura Halstenberg; Lena Mareczek; Jankin Lu; Bonnie Liang; Nadine Gottschalk; Lena K. Mueller (Pharmaceutics)
Background/Objectives: This project aims to provide valuable insights into the formulation of orodispersible films (ODFs) for the delivery of PROTAC ARV-110. The primary objective of this drug delivery formulation is to enhance the solubility of PROTAC ARV-110, which faces significant challenges due to the low solubility of this active pharmaceutical ingredient, as it belongs to a molecular class that is considered to exceed the “Rule of Five”. Methods: We employed the concept of developing a rapidly disintegrating ODF to enhance the solubility of PROTAC ARV-110, utilizing polyvinyl alcohol as the polymer of choice. Given the high thermal stability of ARV-110, the PROTAC was subjected to two primary ODF manufacturing techniques: Hot melt extrusion (HME) and solvent casting. To establish the HME method, pre-screening through vacuum compression molding was performed. The films were characterized based on their disintegration in artificial saliva, drug release in a physiological environment, and mechanical strength. Results: All formulations demonstrated enhanced solubility of ARV-110, achieving exceptional results in terms of disintegration times and resistance to applied stress. Conclusions: The findings from the experiments outlined herein establish a solid foundation for the successful production of orodispersible films for the delivery of PROTACs.